2017
DOI: 10.3346/jkms.2017.32.11.1757
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors Affecting Consumer Acceptance of Accredited Online Health Information

Abstract: With the increasing use of the internet and the spread of smartphones, health information seekers obtain considerable information through the internet. As the amount of online health information increases, the need for quality management of health information has been emphasized. The purpose of this study was to investigate the factors affecting the intention of using accredited online health information by applying the extended technology acceptance model (Extended-TAM). An online survey was conducted from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…This result confirms the studies that consider effectiveness the major contributor or even equivalent to user satisfaction, generally, in information systems [14,51,52]. More specifically, this study parallels the studies that reported effectiveness (sometimes expressed as usefulness) as the most, or one of the most, influential qualities for the satisfaction of patients [53] or health professional users [54-56] in a variety of health information systems. Nevertheless, there exist studies that reached a different conclusion in prioritizing the most influential qualities [57].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result confirms the studies that consider effectiveness the major contributor or even equivalent to user satisfaction, generally, in information systems [14,51,52]. More specifically, this study parallels the studies that reported effectiveness (sometimes expressed as usefulness) as the most, or one of the most, influential qualities for the satisfaction of patients [53] or health professional users [54-56] in a variety of health information systems. Nevertheless, there exist studies that reached a different conclusion in prioritizing the most influential qualities [57].…”
Section: Discussionsupporting
confidence: 86%
“…However, to the best of our knowledge, the studies on health information systems that suggest a kind of satisfaction index with adjusted weights regarding other qualities are limited. Conversely, the studies that have calculated the parameters of TAM or D&M IS models in their contexts or have used a path model that includes user satisfaction alongside other impacted qualities, such as studies by Jo et al, Schaper et al, and Pai et al [53,56,69], implicitly suggest a kind of indexing for adoption and satisfaction aspects. Nevertheless, there are barriers to utilizing the measures suggested for the satisfaction construct.…”
Section: Discussionmentioning
confidence: 99%
“…13 Hanson et al 14 combined four factors (attitude, behavioural intention, behavioural control and subjective norm) to predict the social media adoption behaviours of healthcare centre patients. Finally, Jo et al 15 incorporated seven factors (reliability, barriers, health consciousness, social norm, quality accreditation system, perceived ease of use and perceived usefulness) in their investigation of consumers' acceptance of health information. It is evident that the underlying factors influencing the usage of social media by Australian health consumers are yet to investigated.…”
Section: Social Media In the Australian Healthcare Industrymentioning
confidence: 99%
“…A Google search returned only three studies that applied TAM-based frameworks to understand predictors of adoption behaviours. [13][14][15] McGowan and colleagues (2012) incorporated six factors (perceived usefulness, ease of use, barriers, personal innovativeness, peer access and motivation) when examining the social media adoption behaviour of physicians. The above factors demonstrated a 57% variance in social media usage frequency.…”
Section: Social Media In the Australian Healthcare Industrymentioning
confidence: 99%
“…[23][24][25] However, cancer-related information provided via café websites and blogs is problematic in that it is not tested for scientific merit or the influence of commercial entities posting the information for marketing purposes. 26 Anecdotal information may also be low in 7/11 https://jkms.org https://doi.org/10.3346/jkms.2020.35.e187 trustworthiness and may distort facts. Therefore, there is a need for a systematic process that allows for the sharing of appropriate information.…”
Section: Gap Between Ehealth Literacy Perceptions and Realitymentioning
confidence: 99%